Urban Agglomeration as a Form of Territorial Settlement ("Journal "U". Economy. Management. Finance.", 2016)
The basic concepts of the urban agglomeration, the key stages in the development of agglomerations are discussed in the article. The author identifies the advantages of the agglomeration forms of territorial organization for major business entities.
Keywords: urban agglomeration; the stages of development of urban agglomeration; the advantages of agglomeration of forms of territorial organization; the potential for agglomeration